Eco-sustainable, edible, biodegradable and antioxidant pectin and bacterial cellulose films loaded with coconut oil for strawberry preservation - da Silva Sasaki, Josana Carla [UNESP]; Su, Yanjin [UNESP]; Spinosa, Wilma Aparecida; de Lima Lopes Filho, Paulo Eduardo [UNESP]; Burd, Betina Sayeg [UNESP]; Scontri, Mateus [UNESP]; Tanaka, Jean Lucas [UNESP]; Gonçalves, Rogerio Penna [UNESP]; Felisbino, Bianca Bridi [UNESP]; Dos Santos, Lindomar Soares; Cai, Yi; Mussagy, Cassamo Ussemane; et al. (Elsevier, 2025)
Strawberry is one of the most problematic fresh fruits susceptible to damage or mold due to their sensitive skin. For this, we developed films made of bacterial cellulose [BC, 25 % (w/w)], pectin [P, 75 % (w/w)] loaded with coconut oil for strawberry preservation. XRD patterns of the BC showed three distinct peaks at Bragg angles (2θ) of 14.6°, 16.9°, and 22.7°, indicating the structural characteristics of cellulose I. CG-MS demonstrated that coconut oil contained triacylglycerols like lauric acid, linoleic acid, and dodecanoic acid. Moreover, coconut oil showed antioxidant activity of about 50 % and antimicrobial activity in yeast extracted from strawberries. FTIR spectroscopy, TGA/DTG, mechanical testing, water vapor permeability, AFM and SEM images showed that the oil was successfully incorporated into the film. Next, mass loss and swelling degree and wettability studies revealed that formed films maintained hydrophobic characteristics. In fact, these films presented a high-water vapor barrier because preserved a major part of the characteristics of the biocellulose, turning the bioplastics inert to water. In addition, coconut oil loaded into BC + P bioplastic presented low release due to its hydrophobicity character. Despite this, our bioplastic worked as a mechanical barrier, protecting the fruits from microorganisms and other forms of damage. Furthermore, antioxidant activity from both film-formed was similar (28 %), and these bioplastics preserved the strawberries for 192 h, whereas uncoated fruits degraded at 72 h. Indeed, our bioplastics were more effective in reducing fruit mass loss, especially BC + P + O film. Our findings showed that the essential oil acted as a reducing agent of strawberry mass loss, decreasing its skin transpiration, being an inexpensive and feasible alternative for fruits preservation.